Commentary on Trevor and Huron, "Are Humoresques Humorous? On the Acoustic Similarity Between Laughter and Staccato" - Lee, Christopher S. (Empirical Musicology Review, 2019)
In this commentary, several problematic aspects of Trevor and Huron's study are discussed and suggestions made for improving the experimental design.